Implementation of Students' Character to Have an Attitude as Anti-Sexual Violence Intellectuals Through a Healthy Campus - Nurcahyawati, Enny; Ramliyana, Randi; Rosida, Ida; Puspitasari, Anggun Citra Dini Dwi; Ramdhan, Vickry (Journal of Social Research, 2023)
To address the increasing cases of sexual violence in Indonesia and globally, there is a need to develop comprehensive strategies and initiatives. One approach is to enhance character development within the university environment, specifically through the implementation of a robust Healthy Campus Program. This program aims to instill national character values, focusing on education and higher education settings. The research employs qualitative methods, utilizing both secondary and primary sources, to shed light on the gravity of the issue and potential solutions. This holistic approach addresses not only the intellectual but also the spiritual aspects of individuals, emphasizing the importance of moral values and ethical conduct. It is through education that the foundation for preventing sexual violence can be laid. In addition to formal education, a Healthy Campus Program necessitates active involvement from the entire academic community. This collaborative effort is underscored by the guidelines outlined in Permendikbudristek No. 30 of 2021 concerning Crimes of Sexual Violence. The responsibility to foster a secure environment extends to all stakeholders within the university setting. By integrating character development initiatives and implementing a Healthy Campus Program, universities can contribute significantly to the prevention of sexual violence. This multifaceted approach aims not only to raise awareness but also to cultivate a culture of respect, empathy, and accountability. Through these collective efforts, it is envisioned that the number of sexual violence cases will decrease, creating a safer and more nurturing environment within and beyond university campuses.